Fabrication of Transparent Pb(Mg1/3Nb2/3)O3–PbTiO3 Based Ceramics by Conventional Sintering. Issue 12 (4th September 2013) - Fujii, Ichiro; Yoshida, Ryoichi; Imai, Takahito; Yamazoe, Seiji; Wada, Takahiro; Viehland, D.
<x xml:space="preserve">Abstract</x> Transparent 0.9Pb(Mg1/3Nb2/3)O3–0.1PbTiO3 (PMN‐PT) based ceramics were prepared by a conventional solid‐state synthesis without using a hot‐press method. The ceramics became transparent when they were sintered in an O2 atmosphere. The optical transmission increased with decreasing diameter of the calcined powder, which was controlled by the size of zirconia ball‐milling media. Substitution of 3 mol% La for Pb in PMN‐PT further increased the optical transmission to 68% at the wavelength of 2000 nm, which was comparable to that of hot‐pressed Pb(Mg1/3Nb2/3)O3‐PbTiO3 based transparent ceramics.